2020
DOI: 10.1111/acv.12643
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned odor aversion as a tool for reducing post‐release predation during animal translocations

Abstract: Predation is a key factor in prey population dynamics and could impact population recovery. One common means employed to recover prey populations is that of translocations, but most fail owing to high predation during the early stages. We tested whether conditioned odor aversion can reduce predation during animal translocations by using the predation of the European rabbit Oryctolagus cuniculus by the red fox Vulpes vulpes as a case study. Following a before‐after control‐impact design (BACI), we deployed bait… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 70 publications
0
15
0
Order By: Relevance
“…Predator control is a tool used in both game and conservation management (Reynolds and Tapper 1996; Moreno-Opo et al 2015). In the case of Mediterranean ecosystems, the red fox is one of the most controlled species in managed hunting estates, where it is considered one of the main threats to game species (Delibes-Mateos et al 2013;Tobajas et al 2020b). As this study shows (Table 1), the red fox is one of the main facultative scavenger species in Mediterranean ecosystems (Mateo-Tomás et al 2015;Tobajas et al (in press), so its continuous depletion can reduce the efficiency of rabbit carrion removal, this being especially important at times of high incidence of diseases such as viral hemorrhagic disease that can remain infectious in carcasses for several weeks after death (McColl et al 2002;Henning et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Predator control is a tool used in both game and conservation management (Reynolds and Tapper 1996; Moreno-Opo et al 2015). In the case of Mediterranean ecosystems, the red fox is one of the most controlled species in managed hunting estates, where it is considered one of the main threats to game species (Delibes-Mateos et al 2013;Tobajas et al 2020b). As this study shows (Table 1), the red fox is one of the main facultative scavenger species in Mediterranean ecosystems (Mateo-Tomás et al 2015;Tobajas et al (in press), so its continuous depletion can reduce the efficiency of rabbit carrion removal, this being especially important at times of high incidence of diseases such as viral hemorrhagic disease that can remain infectious in carcasses for several weeks after death (McColl et al 2002;Henning et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Of these studies, two-thirds reported a (partial) success, while field experiments conducted during the season of conflict most often reported failure (Supplementary Data 1). Another option is to artificially increase novelty by adding a new stimulus to a familiar, conditioned stimulus, such as a visual or odor stimulus (Baker et al, 2007(Baker et al, , 2008Tobajas et al, 2021a). For example, domestic chicks avoided a particular taste sooner when a novel color or odor stimulus was added to quinine-flavored water (Roper and Marples, 1997).…”
Section: Exposure Experiencementioning
confidence: 99%
“…It is thus important to implement methods to guarantee long-term or equal palatability. Many CTA interventions do this by regularly replenishing baits or eggs (e.g., Dimmick and Nicolaus, 1990;Indigo et al, 2018;Tobajas et al, 2020aTobajas et al, , 2021a.…”
Section: Stimulus Detectability In Treated Foodmentioning
confidence: 99%
See 1 more Smart Citation
“…Baiting programs are also used in contraceptive or vaccination campaigns of several animal species, to regulate fertility or reduce the incidence of diseases that potentially could affect humans or their economy (Bradley et al 1999;Dı ´ez-Delgado et al 2018). Other uses of baits in wildlife management include live trapping to attract the animals to the traps (Dı ´az-Ruiz et al 2016) and Conditioned Food Aversion (CFA) studies, where a chemical compound is added to baits to elicit its rejection after a non-lethal adverse effect induced by the chemical compound (Tobajas et al 2020b(Tobajas et al , 2021a. CFA with baits has been used to reduce the bait consumption of poisoned baits (Nielsen et al 2015), for monopolisation of baits in vaccination campaigns (Gentle et al 2004), for livestock predation (Gustavson et al 1976;Tobajas et al 2020c) and for post-release predation of prey species (Tobajas et al 2021a).…”
Section: Introductionmentioning
confidence: 99%